2009
DOI: 10.1017/s0022377809990110
|View full text |Cite
|
Sign up to set email alerts
|

A note on the trapped electron dust grain current

Abstract: It is shown that when the non-isothermal trapped electron current is rederived based on the orbit-limited motion theory, the variable dust charge can be expressed in terms of the Lambert function. One can then take advantage of this new transcendental function to illustrate how variable-charge nonlinear trapped dust modes can be investigated semi-analytically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…trapped) electron distribution which is very important for many space and laboratory plasma situations [29][30][31][32][33]. It has been shown that the expression for the electron (dust charging) current is significantly modified by the trapped electron distribution [34,35]. This modified electron current, in turn, may cause a drastic change of the nonlinear features of the DNIA waves.…”
Section: S S Duha B Shikha and A A Mamunmentioning
confidence: 99%
“…trapped) electron distribution which is very important for many space and laboratory plasma situations [29][30][31][32][33]. It has been shown that the expression for the electron (dust charging) current is significantly modified by the trapped electron distribution [34,35]. This modified electron current, in turn, may cause a drastic change of the nonlinear features of the DNIA waves.…”
Section: S S Duha B Shikha and A A Mamunmentioning
confidence: 99%
“…The equation (12) becomes I i0 + I e0 + I n0 = 0. For the negatively charged dust grains, the equilibrium current contributed by trapped electrons I e0 ( ), positive and negatives ions I I , i0 n0 ( ) are based on orbital motion limited (OML) theory are [41][42][43][44]: respectively. To find the equilibrium dust charge q d0 , we have solved I i0 + I e0 + I n0 = 0 this relation via Newton-Raphson method.…”
Section: Basic Equationsmentioning
confidence: 99%
“…where Q d represents the charge of dust and I e (I i ) is the stream of electron (ion) flowing on the surface of dust particles. By assuming that the particles are spherical, I e and I e0 can be given as follows 54 :…”
Section: Governing Equationsmentioning
confidence: 99%
“…The vortex-like electron distribution of the Schamel and Vlasov equation 53 is used to simulate the distribution of electrons in the case of particles being captured. Assuming that the dust particles are charged only by a collection of elementary plasma particles and the fluctuation stream of ion is very small relative to the fluctuation stream of electron, 54 we obtain the kinetic equation of charge of dust particle. In Section 3, the method of multiscale expansion and disturbance analysis 55 are used, and a (3 + 1)-dimensional modified Burgers equation is yielded through a small disturbance.…”
Section: Introductionmentioning
confidence: 99%